Cytological Studies on Two Species, Xanthium strumarium Linn. and Bidens pilosa Linn. Var. minor (Blume) Sherff (Asteraceae-Heliantheae) from Nepal - Karna, Pushpa (International Journal of Applied Sciences and Biotechnology, 2017)
Karyotype, meiosis and pollen stainability of the taxa Bidens pilosa L. var. minor (Blume) Sherff and Xanthium strumarium L. collected from central part of Nepal was cytologically carried out. Results obtained from this investigation showed that chromosome number in somatic cells were recorded to be 2n=36 in Bidens pilosa and 2n=32 in Xanthium strumarium using aceto-orceine squash technique. Likewise haploid chromosome number in reproductive cells were recorded to be n=18 in Bidens pilosa and n=16 in Xanthium strumarium using aceto-carmine squash technique. The range of chromosome length found to be 0.4 to 2.1 µm in Bidens pilosa and 0.4 to 1.6 µm in Xanthium strumarium. Karyotype formula was M16+m2+sm14+st4 for Bidens pilosa and M18+ sm12+st2 for Xanthium strumarium. Based on the position of the centromeres, the chromosomes were categorized into four types with centromere at median point, median region, sub median region and terminal region in Bidens pilosa whereas three types, namely chromosomes with centromere at median point, sub median region and sub terminal region in Xanthium strumarium . In Bidens pilosa karyotype is asymmetrical and slightly asymmetrical karyotype is found in Xanthium strumarium. Absolute length recorded in Bidens pilosa were 19.2µm and 15.8. µm in Xanthium strumarium . Pollen stainability is found to be 94.0 percent in Bidens pilosa and 92.7 percent in Xanthium strumarium. Int. J. Appl. Sci. Biotechnol. Vol 5(1): 66-71